Innovation in Railway Investment Financing Through The Land Value Capture Earmarks Scheme - Safaria, Fery; Firdausy, Carunia Mulya; Najid, Najid (Universitas Negeri Yogyakarta, 2023)
The government of Indonesia is currently working to improve infrastructure, with a particular focus on the railway sector, in order to make transportation more accessible and affordable for all citizens. Therefore, this study aims to determine the reliability of alternative financing for the Land Value Capture (LVC) scheme, especially through earmarks (land tax increase). This scheme is very interesting to examine due to its great implementation potential in Indonesia. In this study, the primary data were obtained from direct measurements in the field of information derived from accessibility factors. Meanwhile, the secondary data were in the form of land price data in the NJOP (Tax Object Sale Value), as well as site structure, and its environment. From this context, the land price forecasting model used the Hedonic method developed into a Log-Log equation and was analyzed by using multiple regression statistical techniques with iterations, to obtain the best model. The LVC calculation also used the calculation formula for Land and Building Tax (PBB), as stated in Governor of Jakarta Regulation No. 77 of 2014. Based on the results, the development stage of the land price forecasting model showed that the independent variables with the most significant contribution (Î± > 0.005) were dominated by accessibility-related factors. In the residential, office, and commercial areas, the maximum increase in land value ranged from IDR 696.8 thousand/m2-IDR 30.5 million/m2, IDR 1.25 million/m2-IDR 41.4 million/m2, and IDR 595.9 thousand/m2-IDR 24.4 million/m, respectively. These estimations were observed with an average increase in the earmarks of all stations at 39.84%. Regarding the initial year of the project operation, the LVC value also obtained the maximum coefficient of the tax difference scheme from 21 stations at IDR 471,941,540,397/year.